Different digestion enzymes used for human pancreatic islet isolation: A mixed treatment comparison (MTC) meta-analysis - Rheinheimer, J.; Ziegelmann, P.; Carlessi, Rodrigo; Reck, L.; Bauer, A.; Leitão, C.; Crispim, D. (Taylor and Francis Inc., 2015)
Collagenases are critical reagents determining yield and quality of isolated human pancreatic islets and may affect islet transplantation outcome. Some islet transplantation centers have compared 2 or more collagenase blends; however, the results regarding differences in quantity and quality of islets are conflicting. Thus, for the first time, a mixed treatment comparison (MTC) meta-analysis was carried out to compile data about the effect of different collagenases used for human pancreas digestion on islet yield, purity, viability and stimulation index (SI). Pubmed, Embase and Cochrane libraries were searched. Of 755 articles retrieved, a total of 15 articles fulfilled the eligibility criteria and were included in the MTC meta-analysis. Our results revealed that Vitacyte and Liberase MTF were associated with a small increase in islet yield (islet equivalent number/g pancreas) when compared with Sevac enzyme [standardized mean difference (95% credible interval - CrI) D -2.19 (-4.25 to -0.21) and -2.28 (-4.49 to -0.23), respectively]. However, all other enzyme comparisons did not show any significant difference regarding islet yield. Purity and viability percentages were not significantly different among any of the analyzed digestion enzymes. Interestingly, Vitacyte and Serva NB1 were associated with increased SI when compared with Liberase MTF enzyme [unstandardized weighted mean difference (95% CrI) D -1.69 (-2.87 to -0.51) and -1.07 (-1.79 to -0.39), respectively]. In conclusion, our MTC meta-analysis suggests that the digestion enzymes currently being used for islet isolation works with similar efficiency regarding islet yield, purity and viability; however, Vitacyte and Serva NB1 enzymes seem to be associated with an improved SI as compared with Liberase MTF.